Evaluating Digital Applications on Smoking Cessation: A Theory-Driven Scoring System from The Transtheoretical Model - Alifia Firliani; Lady Aurelia Laurentzka Hungan; Aleysia Fatira Belami (Jurnal Pendidikan Indonesia, 2024)
Indonesia has one of the highest number of smokers globally and strengthening smoking cessation services one of the key strategies for an effective tobacco control efforts. The rise of digital health has led to an increase in online applications dedicated for smoking cessation. While these online apps offer users valuable opportunities to improve their health decisions, the sheer number of options can make it difficult to find the most suitable app. There is a lack of scientific or theory driven approaches in conducting a systematic evaluation of the available apps. One way to evaluate the effectiveness of existing these apps is looking at them through the lens of behavioral science. Our study aims to assess app effectiveness using dimensions from the transtheoretical model (TTM), a well-known consumer behavioral model. We examined 122 apps from Android and iOS and found that while most incorporate some consumer-behavior insights, they often neglect other key stages of the behavior change journey. While apps support users ready to quit or maintain their commitment, they lack sufficient resources for those contemplating change. Additionally, many miss key features, such as user forums for social support and professional healthcare interactions, that could enhance the apps’ efficacy.